Cell-to-cell signaling through light: just a ghost of chance - Kučera, Ondřej; Cifra, Michal (Cell communication and signaling, 2013)
Despite the large number of reports attributing the signaling between detached cell cultures to the electromagnetic phenomena, almost no report so far included a rigorous analysis of the possibility of such signaling.In this paper, we examine the physical feasibility of the electromagnetic communication between cells, especially through light, with regard to the ambient noise illumination. We compare theoretically attainable parameters of communication with experimentally obtained data of the photon emission from cells without a specially pronounced ability of bioluminescence.We show that the weak intensity of the emission together with an unfavorable signal-to-noise ratio, which is typical for natural conditions, represent an important obstacle to the signal detection by cells.
Keywords: Signal Transduction; pravděpodobnost; Cell Communication; Light; Signal-To-Noise Ratio; elektromagnetické jevy; světlo; Probability; fotony; Photons; signální transdukce; Electromagnetic Phenomena; mezibuněčná komunikace; poměr signál - šum